Successful Management Of Gid Through Surgical Intervention In Goat - Kumar, Amit; Ram , P. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Gid (a disease of central nervous system) is caused by larval stage, Coenurus cerebralis, of adult tapeworm Taenia multiceps. This disease is also known as coenuriasis or stagger. The adult tapeworm reside in small intestine of dog, fox, jackal and other canines (Soulsby, 1986) and the disease is commonly found in caprine and ovine species. The intermediate stage, Coenurous cerebralis, develops in brain and spinal cord of sheep and goat on consuming the fodder soiled with dog’s faeces. The disease is propagated by dogs, final host, consuming the brains of affected animals (sheep/goat) having cystic form of the worm (Amin et al., 2013). There is no effective medicinal treatment against the disease and the affected animals succumb to the disease. However, timely surgical intervention has been hailed as the best remedy to cure the afflicted animals. Magroub (1972) and Aslani (1999) in sheep and Mandal et al. (2004) in goat have reported the cases of coenuriasis which could be successfully treated employing surgical procedures.